Desmatamento na Amazônia brasileira : um olhar sobre a legislação ambiental e seu impacto econômico na economia brasileira - Rampazzo, Daniel Richetti (My University, 2026)
This dissertation examines the application of Brazilian environmental legislation in addressing illegal logging in the Amazon and analyzes the socio-economic impacts arising from this illicit activity. Adopting an interdisciplinary approach that integrates Environmental Law, Economics, Criminology, and Environmental Sciences, the study demonstrates that illegal deforestation is a structurally complex phenomenon sustained by organized criminal networks, institutional weaknesses, and economic pressures that hinder the effective implementation of environmental norms. Although Brazil possesses a comprehensive legal framework, grounded in Article 225 of the Federal Constitution and the National Environmental Policy, the research reveals that the protection of the Amazon biome is limited by institutional deficits, delays in administrative sanctioning procedures, insufficient enforcement capacity, and fragmented federative governance. The study further identifies significant economic impacts, including losses of ecosystem services, climatic instability, reduced productive capacity, and damage to the country?s international credibility. The research also evaluates instruments such as environmental licensing, the Rural Environmental Registry, Payments for Environmental Services, Environmental Reserve Quotas, and carbon market mechanisms, demonstrating their potential to foster conservation-oriented behaviors. The results indicate that combating illegal deforestation requires stable public policies, strengthened institutions, technological modernization, economic incentives, and broad social participation. This dissertation contributes by offering a critical and integrated analysis of the challenges and opportunities necessary to consolidate an effective environmental governance model capable of promoting sustainable development, protecting traditional communities, and ensuring the preservation of the Amazon as an ecological, economic, and strategic asset. [resumo fornecido pelo autor]
A presente dissertação analisa a aplicação da legislação ambiental brasileira no enfrentamento à extração ilegal de madeira na Amazônia e examina os impactos socioeconômicos decorrentes dessa atividade ilícita. Partindo de abordagem interdisciplinar, que articula Direito Ambiental, Economia, Direito Penal e Ciências Ambientais, o estudo evidencia que o desmatamento ilegal configura fenômeno estrutural de elevada complexidade, sustentado por redes criminosas organizadas, fragilidades estatais e pressões econômicas que dificultam a efetiva implementação das normas. Embora o Brasil possua arcabouço jurídico robusto, baseado no art. 225 da Constituição Federal e na Política Nacional do Meio Ambiente, a pesquisa demonstra que a proteção do bioma amazônico é limitada por déficits institucionais, morosidade do processo administrativo sancionador, insuficiência de fiscalização e desarticulação federativa. Identificam-se, ainda, impactos econômicos expressivos, como perdas de serviços ecossistêmicos, instabilidade climática, prejuízos produtivos e danos à credibilidade internacional do país. O estudo também analisa instrumentos como licenciamento ambiental, Cadastro Ambiental Rural, Pagamento por Serviços Ambientais, Cotas de Reserva Ambiental e mecanismos de mercado de carbono, demonstrando seu potencial para induzir comportamentos conservacionistas. Conclui-se que o enfrentamento ao desmatamento ilegal exige políticas públicas estáveis, fortalecimento institucional, modernização tecnológica, incentivos econômicos e ampla participação social. A pesquisa contribui ao oferecer análise crítica e integrada dos desafios e oportunidades para consolidar uma governança ambiental eficaz, capaz de promover desenvolvimento sustentável, proteger comunidades tradicionais e assegurar a preservação da Amazônia como patrimônio ecológico, econômico e estratégico. [resumo fornecido pelo autor]
Keywords: Direito ambiental - Brasil; Desmatamento - Amazônia; Crimes contra o meio ambiente - Amazônia; Madeira - Exploração - Amazônia; Desenvolvimento sustentável.; Environmental Law - Brazil; Clearcutting - Amazônia (Brazil); Offenses against the environment - Amazônia (Brazil); Logging - Amazônia (Brazil); Sustainable development